2009
DOI: 10.1007/s11095-009-9941-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of Screening Methods, Shape Signatures and Engineered Biosensors in Early Drug Discovery Process

Abstract: This work demonstrates an effective combination of computational analysis and simple bacterial screens for rapid identification of potential hormone-like therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…In previous work, we have demonstrated that these biosensors are capable of recognizing hormone like compounds for various human NHR targets, and can differentiate agonistic and antagonistic compounds (Skretas et al,2007). In several cases, drug‐like compounds initially identified by our bacterial sensors, including subtype‐selective agonists and antagonists, have been confirmed in subsequent human cell assays (Skretas et al,2007; Hartman et al,2009).…”
Section: Discussionmentioning
confidence: 65%
“…In previous work, we have demonstrated that these biosensors are capable of recognizing hormone like compounds for various human NHR targets, and can differentiate agonistic and antagonistic compounds (Skretas et al,2007). In several cases, drug‐like compounds initially identified by our bacterial sensors, including subtype‐selective agonists and antagonists, have been confirmed in subsequent human cell assays (Skretas et al,2007; Hartman et al,2009).…”
Section: Discussionmentioning
confidence: 65%
“…These signatures lend themselves to rapid comparison with each other for virtual screening of large chemical databases. Shape Signatures can be used by itself or in conjunction with currently available computational modeling approaches commonly employed in drug discovery and predictive toxicology, such as traditional virtual screening, descriptor-based (e.g., QSAR) models, ligand-receptor docking, and structure-based drug design [52, 6467]. …”
Section: Modeling Frameworkmentioning
confidence: 99%
“…In this work, we describe the fragment-based implementation of Shape Signatures, and demonstrate that it is a powerful tool for computer-aided drug design [812]. Essentially, we prove that the new methodology outperforms the older version by dramatically enhancing its selective power, while retaining all the advantages offered by the original implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction in 2003, the Shape Signatures method [8, 9] has proven a useful tool in a number of drug discovery projects [1012] (including several proprietary investigations). The Shape Signatures technique uses a simple implementation of ray - tracing [13], a method borrowed from computer graphics imaging, to stochastically explore the volume enclosed by the solvent-accessible surface (SAS) of a ligand molecule, or the volume exterior to a protein receptor site.…”
Section: Introductionmentioning
confidence: 99%